2022
DOI: 10.3390/su141912616
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of FinTech Users’ Adoption: Intention and e-Loyalty Post-COVID-19 from a Developing Country Perspective

Abstract: Earlier literature has shown that the implementation of FinTech innovations is not only determined by banks, financial institutions, or government support, but also by the perception and experiences of FinTech users. FinTech research has shown encouraging findings from scholars in developed countries. However, little is known about the users’ acceptance and use of FinTech in Jordan. The aim of this study is to investigate the determinants of users’ intentions and e-Loyalty toward FinTech adoption in Jordan pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 92 publications
9
44
1
Order By: Relevance
“…The findings of this study do not align with other research suggesting that technostress could lower customers' intentions to use Fintech, or, in other words, can prevent consumers from continuing to use Fintech (Lee, 2021;Liébana-Cabanillas et al, 2020;. It happens because the research respondents in this study were only 309, not as many as in earlier studies (Alkhwaldi et al, 2022;Daragmeh et al, 2021), so the research results might be influenced by the number of respondents resulting in different results. Furthermore, the findings of this research suggested that IT mindfulness could increase the intention to use Fintech among consumers of generation Y and Z in Indonesia.…”
Section: Discussioncontrasting
confidence: 97%
“…The findings of this study do not align with other research suggesting that technostress could lower customers' intentions to use Fintech, or, in other words, can prevent consumers from continuing to use Fintech (Lee, 2021;Liébana-Cabanillas et al, 2020;. It happens because the research respondents in this study were only 309, not as many as in earlier studies (Alkhwaldi et al, 2022;Daragmeh et al, 2021), so the research results might be influenced by the number of respondents resulting in different results. Furthermore, the findings of this research suggested that IT mindfulness could increase the intention to use Fintech among consumers of generation Y and Z in Indonesia.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, performance expectancy has a significant impact on users' behavioral intention and this result is validated by prior research findings (Rabaa'i, 2021;Alkhwaldi et al, 2022;Kurniasari et al, 2023), but contradictory results have also been reported (Hassan et al, 2023;Ramprakash et al, 2023). Furthermore, it was found that performance expectancy significantly influences customer satisfaction, and our finding is supported by Chao (2019) and contradicted by Esawe (2022).…”
Section: Findings and Discussionsupporting
confidence: 87%
“…Financial literacy is also used as a moderator between the relationship of effort expectancy, performance expectancy and facilitating condition with behavioral intention. It was found that financial literacy does not moderate the relationship between effort expectancy and behavioral intention and prior study results support our findings (Alkhwaldi et al , 2022; Chan et al , 2022; Alomari and Abdullah, 2023). In addition, the association between performance expectancy and behavioral intention is not moderated by financial literacy and prior studies support our findings (Alkhwaldi et al , 2022; Chan et al , 2022).…”
Section: Findings and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We analyzed and inductively screened 11 evaluation indicators from H1 to H11 according to the detailed division of the elements used for evaluating the first-level indicators ( Table 1 ). To measure indicator B1 (PU), we used the scale developed by Yang et al to set three measurement indicators: content adaptability (H1), content relevance (H2), and content quality (H3) [ 41 ]. To measure indicator B2 (PEOU), we used the scale developed by Gong et al: the technology level (H4), interaction effectiveness (H5), and system compatibility (H6) [ 42 , 43 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%